Use of quince ‘Adams’ rootstock in European pear crop in southern Brazil - Souza D.S.* (2018)
© 2018 International Society for Horticultural Science. All Rights Reserved.Pear is the main fresh fruit imported in volume and value in Brazil, making it an excellent target to the diversification of orchard operations in temperate climate of the subtropical region of Brazil. One of the obstacles to pear cultivation in Brazil are issues related to high vigor plants in southern Brazil conditions. Excess vegetative growth with little floral differentiation can result in a low productive plant, thus requiring the use of dwarfing rootstocks, such as quince (Cydonia oblonga Mill.), whose advantages are reduction in plant vigor, earliness in the bearing stage of production, increased production efficiency and fruit size. Accordingly, this study aimed to research the vegetative and productive aspects of different European pear cultivars grafted with quince ‘Adams’ under the conditions of the mountainous plateau - Santa Catarina state of Brazil. The experimental orchard where the studies were conducted is located in Centro de Ciências Agroveterinárias - CAV, belonging to the State University of Santa Catarina - UDESC, located in the city of Lages, Santa Catarina, 937.73 m of altitude, 27°19’44” latitude and 50°19’44” longitude. The adopted training system was central leader, with planting spaced four meters between rows and one meter between plants, with a total of 2,500 plants ha-1 density. The treatments consisted of different combinations of cultivars of European pear trees with the rootstock quince ‘Adams’. The cultivars used in combination with the rootstock cited above were ‘Abbé Fétel’, ‘Rocha’, ‘Santa Maria’, ‘Packham’s Triumph’ and ‘William’s’. The cultivars did not differ in the trunk diameter and its increment. The cultivar ‘Santa Maria’ had the smallest canopy. Cultivars ‘Rocha’ and ‘Packham’s Triumph’ were the most productive with the highest production efficiency.